Motivation to learn a foreign language in Malaysia - Zubairi, Ainol Madziah; Sarudin, Isarji (Universiti Kebangsaan Malaysia (UKM), 2009)
Many nations have addressed the need to produce graduates who are multilingual in the effort to compete in the global society. Malaysia has acknowledged the importance of proficiency in a third language in order to develop human capital that drives the k-economy as well as competes in the international arena. This study investigated Malaysian students’ motivation to learn a foreign language. Triangulation of methods consisting of survey questionnaire, document analysis and focus group discussion were employed for data collection. A survey based on a 16-item questionnaire was formulated and more than 500 students from University Kebangsaan Malaysia (UKM) and Universiti Teknologi MARA (UiTM) responded to the survey. Responses to the survey were subjected to the Rasch and descriptive analyses in order to capture salient features of students’ responses. The findings of the study indicate that UKM and UiTM students were extrinsically and intrinsically motivated to learn a foreign language. The results of the t-test, however, indicate a significant difference in terms of the motivation of students from the two universities.